Budidaya Tanaman Semusim dengan Pola Tanam Tumpangsari sebagai Langkah Optimalisasi Lahan di Kelurahan Laci Carep, Kabupaten Manggarai: Cultivation of Seasonal Plants with Intercropping Pattern as a Step to Optimize Land in Laci Carep Village, Manggarai Regency - Choirunnisa, Jessyca Putri; Ariefin, Muhammad Noor; Astuti, Tri; Taopan, Rizki Adiputra; Liana, Devi; Adi, Defiyanto Djami; Knaofmone, Elfrida; Wahyu, Yuliana; Jelatu, Silfanus; Mulu, Marlinda; Rofita, Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Utilization of narrow land with intercropping patterns on seasonal crops needs to be done to minimize crop failure and increase farmers' income. The people in Laci Carep Village generally cultivate plants in monoculture (planting one type of plant on cultivated land). The target to be achieved from this activity is to increase the knowledge and skills of the people in Laci Carep Village about cultivating horticultural seasonal crops with intercropping patterns. This activity was carried out in the community in Laci Carep Village, Manggarai, East Nusa Tenggara with a total of twenty participants. The implementation stages of the activity include land surveys, dissemination, field demonstrations, mentoring, and evaluation with pre-tests and post-tests to determine the level of understanding and skills of the participants. The results of this activity show that community knowledge about intercropping patterns increased by 27% and community skills in implementing intercropping patterns on horticultural plants also increased by 35%. This shows that this activity was successfully implemented and right on target.